Kesan suhu dan agen pengkapsul terhadap ciri-ciri fizikokimia serbuk rosel-nanas (hibiscus sabdariffa-ananas comocus) - Ahmad Farimin, Ahmad Osman (2014)
The encapsulation of roselle-pineapple powder by spray drying technique using a laboratory scale spray dryer has been successfully developed. Dried roselle calyces and fresh pineapples were extracted under optimum condition and were mixed (1:1; v/v) to produce the feed for the spray dryer. The feed is formulated by adding 3%, 6%, 9%, 12% and 15% of maltodextrin (MD) DE 10 (w/v) as the encapsulating agent prior to spray drying. Inlet temperatures were varied at 120°C, 140°C, 160°C, 180°C and 200°C, the outlet temperature was set at 80°C and the atomization rate was fixed at 25000 rpm. After the drying process completed, powder was collected at the collection chamber and was analyzed for its physicochemical properties in terms of effects of inlet temperatures and addition of MD. The results showed that the best powder was formed at inlet temperature of 180°C and 12% MD. It produced desirable yield (67.70 ± 2.02%); its ascorbic acid content was high (110.00 ± 1.27 mg/100 g) and its anthocyanins were 1.92 ± 0.17 g/100 g. Powder has low moisture content (5.64 ± 0.23g/100 g), low water activity (0.29 ± 0.08) and high solubility (94.65%). High inlet temperatures reduced up to 34.29% of ascorbic acid content. The inlet temperatures supplied during heating had effectively lowered the moisture content of the powder (range: 4.45% – 15.63%) and its water activity (range: 0.25 – 0.48) thus produced chemically stable powder. It is noted that inlet temperature did not affect the reading of anthocyanins and had no remarkable effect on the solubility of the powder. Optimum formulation of inlet temperature and MD formed less hygroscopic powder (5.03% – 7.23%) but decreased its solubility rate (39 s – 52 s). High MD concentrations (12% and 15%) increased the retention of ascorbic acid up to 80.81%, anthocyanins up to 73.33%, nevertheless reduced the moisture content and the water activity of the powder. This study confirmed that MD is a good encapsulating agent as it shielded the core material by forming continuous shell or matrix with the core material. Acceptability tests showed that powder with inlet temperature of 180°C and 12% MD obtained a score of 70. Therefore, through this study, the spray drying process has resulted in a combination of fruit powder with great physicochemical properties and accepted by consumers. The implication of this study provides basis for the determination of optimum pre-operating parameters of industrial-sized spray dryer in order to produce high quality roselle pineapple powder.